ANALISIS BIOMEKANIKA GERAKAN KARATE TEKNIK TENDANGAN MAWASHI GERI - Nurhadi, Maha Dewi Afifah; Resty, Resty Gustiawati; Wijaya, Habibi Hadi (LP4MK STKIP PGRI Lubuklinggau, 2023)
Martial arts since it was first introduced by Gichin Funakoshi with the term